The Impact of Land Property Right on China’s Rural-urban Migration - Zhao, Yiyang (Transactions on Economics, Business and Management Research, 2024)
The essay discusses China’s transition to state ownership in urban areas and the Household Responsibility System (HRS) in rural regions. It explores how land property rights impact migration, with market mechanisms encouraging migration through land rental opportunities, while government mechanisms hinder it due to land appropriation and insecurity. Utilizing the CHARLS dataset, the study finds that income and gender consistently drive migration, with higher rent per person boosting migration in market systems and appropriation dampening it in government systems. The essay highlights the importance of delineated property rights for urbanization and economic development in China.